Narrativas sobre a educação profissional e tecnológica (EPT) no município de São Gabriel da Cachoeira-AM - Barreto, Roselinda Lima (2023)
Professional and Technological Education (EPT) is a relevant educational modality, foreshadowed in the Law of Guidelines and Bases of National Education (LDB) to promote training in the exercise of professions, help citizens to conquer their place in society, be it white or indigenous, as well as contributing to their insertion in the world of work. Thus, this research aims to investigate the trajectory of Professional and Technological Education in the municipality of São Gabriel da Cachoeira, based on the reports of subjects who experienced this process. The investigation was based on a qualitative research with a narrative approach. We used the narratives as a methodological strategy in understanding the phenomenon based on the experience lived by people in their daily lives. For this purpose, the narrative interview and the documentary survey are part of the data construction techniques, which were analyzed based on the Thematic Analysis. The weaving of this trajectory is told in an e-book, being aligned with this dissertation to cover the historicity of Professional and Technological Education (EPT) in the municipality of São Gabriel da Cachoeira/AM. As a result, we observed that the benefits resulting from the investigation brought return not only to the educational body, in the recognition of history, but also to civil society that benefits from this modality of education, which represents a potent contribution to improving the lives of our participants in the research, both for employees and their children, reverberating change in their thinking and acting, because today they are educators who believe that only through education can we generate the necessary transformation to improve society in São Gabriel da Cachoeira. We leave our research object open so that other paths can be explored, as we bear in mind that no investigation is finished and finished. Finally, by emphasizing the importance of studying this path of the EPT, intertwining history with what was experienced, we want to value and recognize the narratives as integral elements of the social and cultural aspects in the construction of the EPT in São Gabriel da Cachoeira, thus being able to transmit them. them to the generations to come.